Optimalisasi Pengelolaan Wakaf (Studi di Kabupaten Demak) - Riyanto, Riyanto (Universitas Islam Negeri Raden Intan Lampung, 2017)
Waqf, as one of the Islamic social and economic institutions has enormous potentials in encouraging efforts to improve people’s economy. As a country with a huge population and the Muslim majority, Indonesia needs to explore and develops the potential of this religious institution. The combination of religious orders and social values can be utilized as a strong ideological backdrop for the government in managing waqfs so as to grow and be productive. This study tries to examine the status of land endowed in wakaf in Demak district before and after the enactment of Waqaf Law Number 41/ 2004 as well as to identify factors supporting and hindering efforts to optimize wakaf empowerment. This research used a socio-normative approach and it was conducted in several locations within Demak Regency. This study reveals that wakaf institutions in Demak Regency have not been able to improve the welfare of the community. This is because a lot of wakaf land in the area are not managed professionally and productively. Therefore, in the future, it is necessary to develop the professionalism of the Nazir (curator) so that Wakaf institutions can be developed optimally and innovatively to achieve the prosperity of muslim society.